Manifestações neurológicas da toxoplasmose e cinomose em cão jovem - Relato de caso - Galvão, André Luiz Baptista [UNESP]; D'Angelo, Giuliana Tessari; De Vasconcellos, Amanda Leal [UNESP]; De Simone Sfrizo, Luciana [UNESP]; Karcher, Débora Emy [UNESP]; Bresciani, Kátia Denise Saraiva [UNESP]; Tinucci-Costa, Mirela [UNESP] (My University, 2013)
In small animals, toxoplasmosis has been reported in several countries, promoting varied clinical manifestations and uncommon but severe and fatal, which constitute a challenge in the clinical diagnosis of small animals, especially when the nervous system involvement. This infection may be associated with concomitant in infections such as erlichiosis or distemper virus. The objective of this paper is to describe a case of toxoplasmosis and distemper in a border collie bitch, seven months old, with neurological manifestation.
Neurological manifestations of toxoplasmosis and canine distemper in young dog - Case report
Keywords: Immunosuppresion; Protozoan; Zoonosis